Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste

Glance at the chemodiversity of Ocimum species: Trends, implications, and strategies for the quality and yield improvement of essential oil - Gurav, Tanuja P.; Dholakia, Bhushan B.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Ocimum species represent commercially important medicinal and aromatic plants. The essential oil biosynthesized by Ocimum species is enriched with specialized metabolites specifically, terpenoids and phenylpropanoids. Interestingly, various Ocimum species are known to exhibit diverse chemical profiles, and this chemical diversity has been at the center of many studies to identify commercially important chemotypes. Here, we present various chemotypes from the Ocimum species and emphasize trends, implications, and strategies for the quality and yield improvement of essential oil. Globally, many Ocimum species have been analyzed for their essential oil composition in over 50 countries. Asia represents the highest number of chemotypes, followed by Africa, South America, and Europe. Ocimum basilicum L. has been the most widespread and well-studied species, followed by O. gratissimum L., O. tenuiflorum L., O. canum Sims, O. americanum and O. kilimandscharicum Gurke. Moreover, various molecular reasons, benefits, adverse health effects and mechanisms behind this vast chemodiversity have been discussed. Different strategies of plant breeding, metabolic engineering, transgenic, and tissue-culture, along with anatomical modifications, are surveyed to enhance specific chemotypic profiles and essential oil yield in numerous Ocimum species. Consequently, chemical characterization of the essential oil obtained from Ocimum species has become indispensable for its proper utilization. The present chemodiversity knowledge from Ocimum species will help to exploit various applications in the industrial, agriculture, biopharmaceutical, and food sectors.
Keywords: Chemodiversity; Chemotype; Essential oil; Metabolic engineering; Ocimum; Specialized metabolites

Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids